“The dancing pump:” Hypothyroidism with cardiac tamponade – A case report (Indian Journal of Case Reports, 2020)
Hypothyroidism is a common endocrine disorder seen in middle-aged women. Mild pericardial effusion might be seen in patients with unmanaged hypothyroidism but rarely presents with cardiac tamponade and rarely referenced in the literature. Here, we report an unusual case of a 45-year-old female, who presented with breathlessness and was found to have a large pericardial effusion with cardiac tamponade, secondary to hypothyroidism. Treatment included an emergency pericardiocentesis followed by thyroxine hormone replacement.